2021
DOI: 10.1001/jamahealthforum.2021.0264
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Technology Contribute to Disparities in COVID-19 Vaccine Distribution

Abstract: As states have begun administering COVID-19 vaccines to those 65 years and older and essential workers, they face substantial challenges. These challenges include the race against more contagious virus variants; the continuing death toll, particularly in vulnerable subgroups 1 ; concerns about vaccine supplies; and insufficient funding for vaccine distribution. The National Academy of Medicine and the Centers for Disease Control and Prevention's Advisory Council On Immunization Practices (ACIP) have emphasized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 7 publications
0
54
0
Order By: Relevance
“…Patients who did not agree that the vaccine may help fight the pandemic/reduce the virus transmission and those with poor confidence in the healthcare system were also more likely to not support the vaccine. At the time of writing this paper, vaccination process is ongoing at different speeds around the world; some countries are very advanced, others are struggling [ 10 ]. One of the major challenges is vaccine acceptance especially with the important amount of misinformation on the Internet [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who did not agree that the vaccine may help fight the pandemic/reduce the virus transmission and those with poor confidence in the healthcare system were also more likely to not support the vaccine. At the time of writing this paper, vaccination process is ongoing at different speeds around the world; some countries are very advanced, others are struggling [ 10 ]. One of the major challenges is vaccine acceptance especially with the important amount of misinformation on the Internet [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, 56 million children in sub-Saharan African countries experience digital inequality, as the mobile networks do not provide adequate service and experience problems every day. Even in many developed countries, it is stated that millions of school-age students live in homes without Internet service [21][22][23][24][25][26]. In this context, the results of the research conducted by Jaeger and Blaabaek [27] also revealed that COVID-19 has further increased the inequality in learning opportunities and that families with better socioeconomic status are more advantaged than financially more impoverished families during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Estimates have suggested that 80% of people in low-income regions will not be vaccinated in 2021 and that the COVID-19 Vaccines Global Access (COVAX) program will aim to vaccinate only 20% of its target countries by 2021 [4]. Evidence suggests that this may be due to a combination of factors, including a lack of technological resources to effectively distribute and schedule vaccinations [21].…”
Section: Discussionmentioning
confidence: 99%